1976
DOI: 10.1002/path.1711180407
|View full text |Cite
|
Sign up to set email alerts
|

Histological effects of ductal ligation of salivary glands of the cat

Abstract: Forty-two submandibular, 32 sublingual and 31 parotid glands have been examined microscopically after ductal ligation avoiding the nerves for periods from 1 day to 1 yr. After an initial increase in size, there was over-all atrophy in all three glands. In the parotid gland the response was uniform and there was progressive atrophy until most of the acini were extremely atrophic. However, in the submandibular and sublingual glands the response was very variable, and although in some glands most of the acini wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
1

Year Published

1976
1976
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 33 publications
0
32
1
Order By: Relevance
“…There is a similar, experimental situation in which ductal ligation of the sublingual gland of cat with inclusion of the chorda nerve, which causes a parasympathetic denervation, is followed by less extravasation and more atrophy than that in glands in which the chorda is not included in the ligatures. 12,100 The reason for the success of homeopathy in 8 cases of oral ranula in children 31 is unclear, and although the orally administered medicines included hyoscyamine, the dose of 5 ng per tablet would not be expected to significantly inhibit secretory activity. However, spontaneous resolution of oral ranula was observed in 2 children, 21 which emphasizes the variable balance that exists between secretory output from the sublingual gland and the opposing macrophages and granulation and fibrous tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a similar, experimental situation in which ductal ligation of the sublingual gland of cat with inclusion of the chorda nerve, which causes a parasympathetic denervation, is followed by less extravasation and more atrophy than that in glands in which the chorda is not included in the ligatures. 12,100 The reason for the success of homeopathy in 8 cases of oral ranula in children 31 is unclear, and although the orally administered medicines included hyoscyamine, the dose of 5 ng per tablet would not be expected to significantly inhibit secretory activity. However, spontaneous resolution of oral ranula was observed in 2 children, 21 which emphasizes the variable balance that exists between secretory output from the sublingual gland and the opposing macrophages and granulation and fibrous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] They discovered that the extravasated mucus causes an accumulation of macrophages engaged in its removal and the development of granulation and fibrous tissue that restricts and sometimes completely obstructs the extravasation. Thus Baurmash advocated marsupialization and packing the cavity with gauze so that the leak would be immediately obstructed, and the foreign-body reaction provoked by the gauze would lead to fibrosis and a permanent seal.…”
mentioning
confidence: 98%
“…Bonet-Coloma et al [35] reported that 22 cases of intraoral ranula were performed by incision with a tract dilator in children; then, 18.2% (4/22) of cases recurred at a mean of 12 months after treatment. Previous studies indicated that incision followed by drainage frequently causes recurrence because of the early closure of the incised portion [39], persistent extravasation of sublingual gland and without the development of granulation and fibrous tissue that obstructs the extravasation [40,41]. Rolled gauze was placed at the submandibular region to apply continuous pressure for 3 weeks.…”
Section: Incision and Drainagementioning
confidence: 99%
“…Previous experimental studies investigating atrophy and development of salivary glands suggested that parasympathetic nerves are important for the maintenance and development of salivary glands. For example, parasympathectomy of salivary glands (Poat and Templeton, 1982;Hironaka et al, 2003;Carpenter et al, 2005) or damage to parasympathetic nerves by ligation (Harrison and Garrett, 1976;Harrison et al, 2001) induced salivary gland atrophy. Furthermore, cellular proliferative activity in salivary glands was enhanced by electrical stimulation of parasympathetic nerves (Schneyer et al, 1993) and administration of pilocarpine, a parasympathomimetic agent (Burlage et al, 2009).…”
Section: Discussionmentioning
confidence: 99%